Export Performance Of Indonesia's Leading Tropical Fruit Commodities To Main Destination Countries - Ganjar Widhiyoga; Hasna Wijayati; Ririn Alma’unah (LPPM ISNJ Bengkalis, 2023)
As an agricultural country, Indonesia has the potential in terms of the quantity of tropical fruit production to dominate the international trade market. This study analyzed the export performance of Indonesia's superior tropical fruit commodities to the central export destination countries from 2013 to 2020. This study used a descriptive quantitative method. The data source used is primary data in unstructured interviews, secondary data in documentation, and literature study. Interviews were conducted with representatives of PT. Laris Manis Utama and Balitjestro Malang as informants. Documentation data was obtained from the Ministry of Agriculture and the Central Bureau of Statistics (BPS) database. In contrast, literature study data was obtained from journals, books, online news, and related research topics. Data analysis techniques using descriptive statistical analysis. The study results show that from 2013 to 2020, mangosteen, mango, and orange experienced an increase in export performance, while guava experienced a decrease in export performance. This research shows that Indonesia has great potential in the tropical fruit sector. However, to optimize this potential, support from upstream to downstream is needed to maximize the value added to commodities.